Students’ Perception on the Implementation of Jumbled Words to Reinforce Their Grammar Mastery at the Eighth Grade of SMPN 15 Padang - Nurmela, Nurmela; Rani, Yati Aisya (Universitas Negeri Padang, 2024)
This study aimed to find out the students’ perception on the implementation of Jumbled Words to reinforce their grammar mastery at the eighth grade of SMPN 15 Padang. This research used descriptive method. The sample of this study was the students of VIII.5 class who were selected used purposive sampling. Questionnaires and interviews were used to collect the data. Questionnaires as the main instrument and interviews as the strengthening instrument. The results of this study showed that most of the students had a positive perception on the implementation of Jumbled Words to reinforce their grammar mastery. Despite the fact that the perception of most of the students was very positive, there were still some students who disagreed with this thing. After conducting interviews, it was discovered that the reason they gave a negative perception of jumbled words was because basically they did not understand grammar. Their lack of understanding of grammar made them hated the lesson, which ultimately caused them to have a negative perception on the learning activity implemented in teaching grammar itself. Therefore, teachers are expected to pay more attention to students who give negative perceptions, in other words those who do not understand grammar. Apart from that, teachers are also expected to be able to provide great learning activities in teaching grammar to students. Thus, whatever learning activities are applied in grammar learning later, they can enjoy it.